Investigation of microstructure and wear resistance of laser-clad CoCrNiTi and CrFeNiTi medium-entropy alloy coatings on Ti sheet. (January 2022) - Xiang, Kang; Chai, Linjiang; Zhang, Chengquan; Guan, Haotian; Wang, Yueyuan; Ma, Yanlong; Sun, Qi; Li, Yuqiong
Highlights: Two laser-clad MEACs (CoCrNiTi and CrFeNiTi) were successfully prepared on pure Ti sheet. Both MEACs are mainly comprised of BCC phase along with interdendritic Cr2 Ti Laves phase. Hardness and wear resistance of both MEACs are markedly improved compared to the substrate. Their superior properties are related to solid-solution, short-range order, grain refinement and the Laves phase. Abstract: Two medium-entropy alloy coatings (MEACs), CoCrNiTi and CrFeNiTi, were successfully prepared on pure Ti sheet by utilizing pulsed laser cladding. Microstructural characterization reveals that both the MEACs are mainly comprised of BCC solid-solution phase along with interdendritic Cr2 Ti Laves phase (C14 type) due to element segregation. Hardness and wear tests show that the CoCrNiTi MEAC has a hardness of 762 ± 32 HV and a specific wear rate of 1.7 × 10 −5  mm 3 ·N −1 ·m −1, and those of the CrFeNiTi MEAC are 820 ± 34 HV and 2.8 × 10 −5  mm 3 ·N −1 ·m −1, respectively, both of which are markedly superior to the pure Ti substrate (114 ± 5 HV and 5.4 × 10 −4  mm 3 ·N −1 ·m −1 ). Comprehensive analyses suggest that the excellent properties of the MEACs can be attributed to combined strengthening effects of solid-solution, short-range order, grain refinement and the Cr2 Ti Laves phase.